Cardiac Imaging in Patients After Fontan Palliation: Which Test and When? - Ciliberti, Paolo; Ciancarella, Paolo; Bruno, Pasqualina; Curione, Davide; Bordonaro, Veronica; Lisignoli, Veronica; Panebianco, Mario; Chinali, Marcello; Secinaro, Aurelio; Galletti, Lorenzo; Guccione, Paolo (Frontiers in Pediatrics, 2022)
The Fontan operation represents the final stage of a series of palliative surgical procedures for children born with complex congenital heart disease, where a “usual” biventricular physiology cannot be restored. The palliation results in the direct connection of the systemic venous returns to the pulmonary arterial circulation without an interposed ventricle. In this unique physiology, systemic venous hypertension plays the main role for propelling blood through the pulmonary vasculature. Although the Fontan operation has dramatically improved survival in patients with a single ventricle congenital heart disease, significant morbidity is still a concern. Patients with Fontan physiology are in fact suffering from a multitude of complications mainly due to the increased systemic venous pressure. Consequently, these patients need close clinical and imaging monitoring, where cardiac exams play a key role. In this article, we review the main cardiac imaging modalities available, summarizing their main strengths and limitations in this peculiar setting. The main purpose is to provide a practical approach for all clinicians involved in the care of these patients, even for those less experienced in cardiac imaging.